Prognostic impact of low muscle mass and low muscle density in patients with diffuse large B-cell lymphoma. Issue 7 (6th June 2020) - Rier, Hánah N.; Kharagjitsing, Hardjit; van Rosmalen, Joost; van Vugt, JLA; Westerweel, Peter E.; de Jongh, Eva; Kock, Mark; Levin, Mark-David
Abstract: Low muscle mass (LMM) and low muscle density (LMD) are increasingly recognized as prognostic factors for survival in different malignancies. This study determined the association of LMM and LMD with survival in DLBCL (diffuse large B-cell lymphoma) patients. CT-based measurement of muscle was performed in 164 DLBCL patients prior to chemo-immunotherapy. Z -scores adjusted for gender, age, and body mass index were derived from a healthy reference population. LMM or LMD were defined as a Z -score below −1 and were related to OS and PFS. The co-existence of both LMM and LMD was observed in 13% of the DLBCL patients and was significantly associated with shorter OS and PFS. Also, these patients more often did not complete the planned treatment. The combination of LMM and LMD is an independent prognostic factor for survival in DLBCL patients. This may guide clinical decision-making in patients with suspected insufficient performance to benefit from chemo-immunotherapy in standard doses. Key points: Patients with DLBCL have low muscle mass (LMM) and low muscle density (LMD) compared to healthy counterparts. The combination of LMM and LMD is a negative prognostic factor for survival, independent of comorbidities and unfavorable lymphoma characteristics.